2019
DOI: 10.1186/s42269-019-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

A facile nano-iron oxide sensor for the electrochemical detection of the anti-diabetic drug linagliptin in the presence of glucose and metformin

Abstract: Background: A highly sensitive sensor for the electrochemical determination of an antidiabetic drug Linagliptin (LG) was constructed using carbon paste electrode (CPE) modified with iron oxide nanoparticles (Fe 2 O 3 NPs). The electrochemical performance of LG was examined analytically, and some dynamics were considered for the first time. Results: This work indicates that the oxidation reaction of LG on CPE/Fe 2 O 3 NPs is a one electron and one proton process, which is controlled by both diffusion and adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Using this method, a slope value of 0.43 was achieved, which is less than the theoretical value of 1.0 that was anticipated to occur at the surface of the electrode. Furthermore, this supports the notion that, following the adsorption of the glucose molecules, the entire electrode process is primarily controlled by diffusion [ 46 ] because the lower actual slope (0.43) than the predicted value may be due to glucose molecules' partial participation in the HPMpFP-graphene/GCE response.…”
Section: Resultssupporting
confidence: 76%
“…Using this method, a slope value of 0.43 was achieved, which is less than the theoretical value of 1.0 that was anticipated to occur at the surface of the electrode. Furthermore, this supports the notion that, following the adsorption of the glucose molecules, the entire electrode process is primarily controlled by diffusion [ 46 ] because the lower actual slope (0.43) than the predicted value may be due to glucose molecules' partial participation in the HPMpFP-graphene/GCE response.…”
Section: Resultssupporting
confidence: 76%
“…7C ). It is also observed that oxidation peak potential (Epa) of FAV shifted towards the positive direction with the increase of the scan rate, which suggests the expected result for an irreversible electrode reaction [ 68 ]. The number of electrons transferred in the oxidation step of FAV can be calculated by Laviron’s equation from the slope of Epa vs. natural logarithm of scan rate (ln v) plot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…47 Also, and from economical view, we can ensure that our procedure for LNG voltammetric determination is better since we use PGE as a working electrode which characterized as the lowest cost, ease of availability, good mechanical rigidity and it gives results with high repeatability values. Although the suggested method is less sensitive than the previously reported for the LNG voltammetric determination 22 , the sensitivity achieved is fully sufficient to determine LNG either in bulk solutions, pharmaceutical formulations or in spiked biological samples. Moreover, using the proposed method LNG was determined at a short time of analysis with no need for complex extraction steps.…”
Section: Analytical Applicationmentioning
confidence: 82%
“…The tabulated data shows that the obtained results using the proposed method are very close or even better than the results obtained by other reported classical methods. To the best of our knowledge, the literature showed only one article for the electroanalytical determination of LNG 22 , where carbon paste electrode (CPE) is modified with iron oxide nanoparticles (Fe2O3NPs) and it was applied as an electrochemical sensor for LNG determination. There is no doubt the use of metallic nanoparticles as an electrode modifier increases the electroanalytical procedure sensitivity which resulting in lowers LLOD and LLOQ.…”
Section: Analytical Applicationmentioning
confidence: 99%